Meta-analysis of the efficacy of the erector spinae plane block after spinal fusion surgery - He, Yi; Liu, Heng; Ma, Peng; Zhang, Jing; He, Qiulian (PeerJ, 2024)
Objective To investigate the efficacy of erector spinal plane block (ESPB) after spinal fusion surgery in this study. Methods The PubMed, Embase, Cochrane library, and Web of Science databases were searched with a search deadline of March 30, 2024, and Stata 15.0 was used to analyze the data from the included studies. Result Nine randomized controlled trials involving 663 patients were included. Meta-analysis showed that EPSB could reduce pain scores at 2h (standard mean difference (SMD) = −0.78, 95% CI [−1.38 to −0.19], GRADE: Moderate), 6 h (SMD = −0.81, 95% CI [−1.23 to −0.38], GRADE: Moderate), 12 h (SMD = −0.59, 95% CI [−1.05 to −0.13], GRADE: Moderate), 24 h (SMD = −0.54, 95% CI [−0.86 to −0.21], GRADE: Moderate), 48 h (SMD = −0.40, 95% CI [−0.75 to −0.05], GRADE: Moderate) after spinal fusion surgery, as well as the PCA (analgesia medication use) (SMD = −1.67, 95% CI [−2.67 to −0.67], GRADE: Moderate). However, EPSB had no effect on intraoperative blood loss (SMD = −0.28, 95% CI [−1.03 to 0.47], GRADE: Low) and length of hospital stay (SMD = −0.27, 95% CI [−0.60–0.06], GRADE: Low). Conclusion Combined with the current findings, EPSB may reduce pain scores in spinal fusion surgery, possibly reducing the use of postoperative analgesics. However, due to the limitations of the study, we need more high-quality, multi-center, large sample randomized controlled trials to merge.
Keywords: Erector spinae plane block; Spinal fusion surgery; Meta-analysis